Pengaruh Artificial Intelligence dan Literasi Digital Terhadap Kinerja Karyawan di Bidang Ekonomi - Prasetio, Tio (LPPM Universitas Bina Sarana Informatika, 2024)
The development artificial intelligence will have impact on all employment sectors, one of which is economic sector. The threat many jobs being replaced by artificial intelligence has raised concerns about the decline in performance company employees. The aim research is to analyze and provide empirical evidence influence of artificial intelligence and digital literacy on employee performance in the economic sector. The research method used was quantitative with sample 235 people from 28 companies. The research results show that artificial intelligence has significant influence on employee performance. This is because artificial intelligence has changed the way employees work to become faster, more effective, accurate and innovative. So that the way working has impact on employee performance by producing better and maximum output quality and quantity work. And digital literacy has significant influence on employee performance. This is caused by employees' digital abilities in utilizing technology which has impact on the quality work and better work initiatives. So that digital literacy possessed by employees can influence employee performance to be more optimal. The novelty in this research uses research objects in economic companies such as accounting, taxation, auditing, accounting software, statistics and banking and uses examples of artificial intelligence applications related to the respondent's position in this research, such as virtual assistants, search engines, chatbots, etc.